Oxygen requirements in multisystem inflammatory syndrome in children admitted in tertiary care hospital of North India - Sood, Ambika; Sharma, Deepak; Katoch, Raju; Sharma, Rakesh; Sharma, Sanya; Kaushik, Dipesh (International Journal of Research in Medical Sciences, 2022)
Background: Study was aimed to describe the oxygen requirements among children admitted as multisystem inflammatory syndrome in children (MIS-C) in Indira Gandhi Medical College, Shimla. Methods: We conducted a cross-sectional study, from January 2021 to July 2021, in the pediatric ward of Indira Gandhi Medical College (IGMC), Shimla. Children admitted with a diagnosis of MIS-C were included. Data regarding socio-demographic factors and oxygen requirements were extracted and analyzed using Epi Info V7 software. Results: A total 31 children diagnosed as MIS-C were included. Tachypnea was present in 18 (58.1%) respiratory distress in 15 (48.4%). Optimal oxygen saturation (SpO2) more than 94% in 9 (25.8%), 93-94% in 8 (25.8%), 91-92% in 5 (16.1%), 86-90% in 2 (6.5%), 81-85% in 4 (12.9%), 75-80% in 1 (3.2%), 71-75% in 1 (3.2%) and <60% in 1 (3.2%). Oxygen at the rate of 2 l/min in 1 (3.2%), 3 l/min in 2 (6.5%), 4 l/min in 1 (3.2%), 5 l/min in 5 (16.1%) and 10 l/min in 9 (29.0%), was given through nasal prong in 1 (3.2%), Venturi mask in 3 (9.7%), NRM in 7 (22.6%) and mechanical ventilation in 7 (22.6%). Duration was for 2 days in 4 (12.9%), for 3 days in 7 (22.6%), for 4 days in 3 (9.7%), for 7 days in 1 (3.2%), for 10 days in 1 (3.2%), for 11 days in 1 (3.2%) and for 13 days in 1 (3.2%). Ventilatory support was given to 7 (22.6%), for 4 days in 2 (6.5%), for 7 days in 2 (6.5%), for 10 days in 1 (3.2%), for 11 days in 1 (3.2%) and for 13 days in 1 (3.2%). Conclusions: Oxygen is a crucial component of MIS-C therapy, children, observing a dip in SpO2 level should immediately start oxygen therapy.